2006
DOI: 10.1084/jem2034oia13
|View full text |Cite
|
Sign up to set email alerts
|

CpG-induced tyrosine phosphorylation occurs via a TLR9-independent mechanism and is required for cytokine secretion

Abstract: "CpG-induced tyrosine phosphorylation occurs via a TLR9-independent mechanism and is required for cytokine secretion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The pathway involved in the recognition of circulating nucleosomes is therefore different from the classical pathway involved in the recognition of CpG‐ODN. The fact that CpG motifs are not involved indicates that nucleosome recognition does not occurs via a CpG‐induced but TLR9‐independent mechanism 31. Importantly, similar results were obtained when we activated normal PMN with SLE plasma, whereas nucleosome‐depleted lupus plasma was not stimulatory, showing that the activation was specifically mediated by circulating nucleosomes.…”
Section: Discussionsupporting
confidence: 72%
“…The pathway involved in the recognition of circulating nucleosomes is therefore different from the classical pathway involved in the recognition of CpG‐ODN. The fact that CpG motifs are not involved indicates that nucleosome recognition does not occurs via a CpG‐induced but TLR9‐independent mechanism 31. Importantly, similar results were obtained when we activated normal PMN with SLE plasma, whereas nucleosome‐depleted lupus plasma was not stimulatory, showing that the activation was specifically mediated by circulating nucleosomes.…”
Section: Discussionsupporting
confidence: 72%
“…We demonstrated that Syk directly associates with TLRs (TLR3, TLR4, and TLR9) and various downstream adaptor molecules and kinases, including MyD88, TRIF, TRAF3, TRAF6, TAK1, and TBK1. Previous studies showed that Syk is recruited to activated TLR4 and TLR9 (23,25). Here, we examined whether Syk was involved in determining the balance between inflammatory and antiinflammatory responses.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies demonstrated that TLR ligands, such as polyinosinicpolycytidylic acid [poly(I:C)], LPS, lipoprotein, CpG (9,(22)(23)(24)(25)(26)(27), and minimally oxidized low-density lipoprotein (LDL) (28,29), as well as factors such as TNF-a (30)(31)(32), can activate Syk. Activation of cells with LPS and minimally oxidized LDL enables Syk to interact with TLR4 (33)(34)(35), MyD88, TRIF (36), and TRAF6 (37).…”
Section: Introductionmentioning
confidence: 99%
“…The TLR‐signalling adaptors, Mal and Myd88, can be tyrosine‐phosphorylated by PTK 14, 15, suggesting that ITAM and ITIM play a regulatory role in TLR‐mediated responses to pathogens, but in what molecular context? Interestingly, DAP12 encodes a consensus ITIM "SPYQEL" within the ITAM, centred about the membrane proximal tyrosine (Table 1).…”
Section: Closet Itim?mentioning
confidence: 99%